Association Between the Low Levels of Vitamin D and Treg Function in Systemic Lupus Erythematosus Patients - Kusworini Handono; Dona Marisa; Handono Kalim (Acta Medica Indonesiana)
Aim: to determine the relationships between vitamin D and CCR4 expression on Treg, and Treg migratory capacity in SLE patients in Indonesia. Methods: vitamin D level assesment, CCR4 expression on Treg and Treg migratory capacity were performed on 41 SLE patients and 20 healthy controls. Serum vitamin D levels were measured by ELISA (Cusabio). The expression of CCR4 on Treg was detected by flow cytometry and Treg migratory capacity was performed in chemotaxis chamber using CCR4 ligands, TARC and MDC, and subsequently analyzed by flow cytometry using FACS Calibur (Becton Dickinson). The number of migrated Treg is the ratio of CD4+CD25+CCR4+ cells number in lower chamber of chemotaxis compared to the total number of CD4+CD25+CCR4+ cells before migration, and stated in percentage. Results: vitamin D levels were significantly lower in SLE patients compared with healthy controls (p=0.000). The vitamin D levels were positively correlated to the percentage of migrated Treg toward TARC (p=0.015) and MDC (p=0.000), but there was no difference in Treg CCR4 expression between SLE patients and healthy controls. Conclusion: low vitamin D levels cause reduced Treg migratory capacity in SLE patients and healthy people. This influence occurs through other factors rather than CCR4 expression.